2016
DOI: 10.1136/gutjnl-2015-310752
|View full text |Cite|
|
Sign up to set email alerts
|

Signalling via the osteopontin and high mobility group box-1 axis drives the fibrogenic response to liver injury

Abstract: ObjectiveLiver fibrosis is associated with significant collagen-I deposition largely produced by activated hepatic stellate cells (HSCs); yet, the link between hepatocyte damage and the HSC profibrogenic response remains unclear. Here we show significant induction of osteopontin (OPN) and high-mobility group box-1 (HMGB1) in liver fibrosis. Since OPN was identified as upstream of HMGB1, we hypothesised that OPN could participate in the pathogenesis of liver fibrosis by increasing HMGB1 to upregulate collagen-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
112
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(132 citation statements)
references
References 26 publications
6
112
1
Order By: Relevance
“…Studies have shown that measuring OPN in the plasma of liver disease patients is an effective biomarker for assessing the severity of liver fibrosis [811]. Furthermore, it has been demonstrated that hepatocytes act as a major source of OPN, and act in a paracrine role in activating HSCs and increasing collagen-I production [12]. Multiples studies have found that neutralizing OPN abrogates the development of fibrosis [4, 5, 1215].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that measuring OPN in the plasma of liver disease patients is an effective biomarker for assessing the severity of liver fibrosis [811]. Furthermore, it has been demonstrated that hepatocytes act as a major source of OPN, and act in a paracrine role in activating HSCs and increasing collagen-I production [12]. Multiples studies have found that neutralizing OPN abrogates the development of fibrosis [4, 5, 1215].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that hepatocytes act as a major source of OPN, and act in a paracrine role in activating HSCs and increasing collagen-I production [12]. Multiples studies have found that neutralizing OPN abrogates the development of fibrosis [4, 5, 1215]. In a murine model of thioacetamide (TAA)-induced hepatic fibrosis, OPN-knockout mice demonstrated less hepatic damage and a faster resolution of fibrosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…The first involves the acetylation of HMGB1 by extracellular osteopontin (OPN), a stress sensor protein that is enhanced in liver disease and elevated in serum of patients who are at risk of HCC development [44]. Acetylated HMGB1 interacts with HDAC1/HDAC2 to promote collagen-I expression by HSCs and increase its histological deposition [45]. The second mechanism relies on the upregulation of the Gas6/Axl pathway in HSC leading to activation of these cells and liver fibrogenesis upon carbon tetrachloride-induced injury in mice [46].…”
Section: Hcv-induced Inflammatory Responses Indirectly Driving Hepatomentioning
confidence: 99%
“…The second mechanism relies on the upregulation of the Gas6/Axl pathway in HSC leading to activation of these cells and liver fibrogenesis upon carbon tetrachloride-induced injury in mice [46]. Importantly, the clinical relevance of both mechanisms was evidenced by the correlation between the severity of liver injury and increased expression of OPN/HMGB1 or Gas6/Axl, respectively, in HCV-infected patients [45,46]. However, additional clinical cohort studies may be required to corroborate the involvement of these processes in HCV pathogenesis.…”
Section: Hcv-induced Inflammatory Responses Indirectly Driving Hepatomentioning
confidence: 99%
“…Fibrosis in kidney results in chronic kidney disease [8]. Fibrosis in liver accounts for cirrhosis and hepatocellular carcinoma [9]. Simultaneously, vascular remodeling may lead to arteriosclerosis [10].…”
Section: Introductionmentioning
confidence: 99%